Draft Ninth Five Year Plan (1997-2002) and Annual Plan (1997-98) Union Territory of Dadra and Nagar Haveli - Planning Commission (Planning Commission, 1997)
The Planning Commission has, in view of the demographic and international relation in respect of trade and commerce and the latest global developments, emphasised to keep meaningful and positive approach during the IXth Five Year Plan which include interalia the following at the time of doing ground work for this Plan period.
Department of Planning and Statistics, Union Territory Administration of Dadra and Nagar Haveli